Enhancing Conventional Rehabilitation Monitoring in South Africa by Adding Landscape Function Characteristics - Haagner, A.S.H.; Kellner, K.; Tongway, D.J. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
South African legislation requires mines to address all residual pollutant impacts and to initiate an end land- use that conforms to the concept of sustainable development, before they can be considered for closure. The conventional vegetation for gold tailings in South Africa involves grass planting into ameliorated tailings, and is primarily used for dust control and stabilization. This herbaceous layer has only recently received focus as an asset for closure and sustainable land-use. In addition, the conventional criteria used to demonstrate erosion control and persistence by this vegetation on gold tailings, such as grass basal cover and species number, may also be insufficient for closure purposes. Landscape function analysis (LFA) is a means of assessing the functionality of rehabilitated sites in terms of their ability to retain mobile resources, and relies upon measures of substrate stability, infiltration and nutrient cycling. LFA may complement or replace conventional vegetation sampling for species and composition. LFA indices are considered to reliably represent the ecological status of a rehabilitated site as they include measures of ecosystem function. We used LFA to assess the sustainability of vegetation on a chronosequence of rehabilitation sites at two gold tailings storage facilities. The surveys were conducted over two growth seasons to determine the temporal and spatial resource availability patterns, linked to seasonal changes in vegetation structure, function and composition. Sample sites were characterized on a continuum from least to most functional landscapes, and compared in terms of vegetation cover, species composition and substrate properties. The indices of landscape function were consistent across the continuum, as was landscape organization, an index of the leakiness of a landscape. Results showed that it was still too early for LFA or vegetation monitoring to predict rehabilitation trajectories, but did show that rehabilitation progress in even the oldest sites was still in its very early stages. The main limiting functionality indices were nutrient cycling and infiltration, both which required greater litter deposition and biological activity to enhance function. This was supported by litter and perennial vegetation cover being most significant in separating the more functional from less functional sites. There were no clear relationships between rehabilitation age, landscape function and plant community development, with both techniques showing the rehabilitation to be in early successional stages. LFA, in combination with vegetation monitoring, has the potential to anticipate landscape deterioration at an early stage on tailings, and to guide the most effective ameliorative actions. Although LFA is not widely used as a tool for monitoring rehabilitation of tailings in South Africa, this project illustrates that it does hold potential for assessing the functionality of rehabilitation for closure purposes.